ANALISIS YURIDIS DAN NORMATIF TANAH WAKAF DALAM HUKUM ISLAM DAN UNDANG-UNDANG WAKAF INDONESIA - Aequo, Najwa Yustitia; Aisya, Alayya Rihadatul; Syavitri, Amellia Intan; Nuraina, Astri; Fajri, Naura Nurul; Azizah, Aulia Nur; Angelica, Devina; Aldy , Muhammad (Gapenas Publisher, 2025)
Wakaf is a transfer of ownership of personal property of a wakif or wakaf giver changing its ownership status to public property in its benefits through the waqf recipient. The reflection of wakaf becomes a representation of a Muslim to Allah SWT, and reflects social responsibility towards others. Wakaf assets managed by nazhir who is a person or institution responsible for managing wakaf assets so that they have value for society according to Islamic law using two main approaches, social wakaf and productive wakaf. This study is to examine waqf land in Islamic law and wakaf laws in Indonesia based on legal and normative reviews. The purpose of this study is to see the legal reflection of wakaf land based on the concept of Islamic law by considering the wakaf law in Indonesia. The method used in this study is the normative research method, which is carried out by means of interpretation of the legal materials that have been collected. The results of this study conclude that wakaf can be carried out with the concept of Islamic law by considering the wakaf laws in indonesia